Comparative study of brackishwater species in Peninsular Malaysian - Ramzani, Sara Ravan; Ismail, Mohd Mansor; Abdurofi, Ilmas (Scholars Research Library, 2013)
The importance of aquaculture as a means of supplying the predicted shortfall of fisheries and other aquatic products has been increasingly proposed. It would appear certain that the increased demands of growing populations must be met from aquaculture farms in which outputs can be increased from selected productive inputs. Brackish water farming in Malaysia is one of the fast growing segments of the economy In spite of the fact that brackish water culture had relatively rapid growth in the last decade, due to increase in production cost and decrease in international price, the profit of aquaculture production has decreased in recent years. The purpose of this research is to analyze the competitiveness of Malaysian three main species brackish water farming on the Peninsular. The comparative advantages method was used to investigate divergence between market and social profit in the Malaysian aquaculture industry. The results indicated that social prices for production cost were higher than market prices for fuel, electricity, fertilizer and less than market price for feed. It indicates that in spite of government subsidies to shrimp production inputs, the shrimp producers categorized as taxpayers for total input cost. In addition, it was concluded that shrimp social price and production profit were less than market prices. The conclusion drawn is that provide guidance for Malaysian policy makers can offer important advantages of controllability, market adaptation, greater appreciation of their comparative roles and help retain aquaculture entrepreneurs and investors domestically.